Sustainable bioethanol production by solid-state fermentation: a systematic review - Nur Fathin, Ruslan; Noormazlinah, Ahmad; Azlan, Abas; Sanfilippo, Antonio; Mahmoud, Khaled; Mimi Sakinah, Abdul Munaim; Nour, Abdurahman Hamid (Springer, 2024)
The escalation of the global population has accelerated the demand for sustainable energy sources such as bioethanol. Traditionally, bioethanol was obtained by the fermentation of sugar from agricultural crops and grains. However, this technique creates serious threats on the global food supplies, thus hindering the commercial production of bioethanol. Therefore, there is a need to develop new technologies and low-cost raw materials in order to ensure that bioethanol is economically comparable to the first generation of bioethanol. Solid-state fermentation (SSF) has been in the limelight within the scientific community because of its efficiency, cost-effectiveness, and promising technology to produce bioethanol. SSF involves the cultivation of microorganisms on a solid substrate in the absence of free-flowing water, which eliminates the need for sugar extraction and reduces wastewater production. This systematic review provides an overview of the applications of SSF in bioethanol production while presenting recent studies and advancements of this technology for producing sustainable and cost-effective bioethanol.